Organizational Learning Culture and Work Engagement: A Moderated Mediation Model of Abusive Supervision and Employee Resilience - Sari, Gunisya Kartika; Salendu, Alice; Faidhil, M (TAZKIYA Journal of Psychology, 2025)
The organizational learning culture is crucial for enhancing overall performance and fostering employee engagement. By promoting a culture of learning, organizations can generate positive emotions among employees, which helps build resilience. However, abusive supervision from management can undermine this resilience, decreasing employee involvement in their work. This study focuses on the impact of organizational learning culture on work engagement, exploring how this relationship is influenced by abusive supervision and mediated by employee resilience. Data were collected from 206 employees across various public and private sectors in Indonesia. The research hypothesis was tested using models 4 and 7 from the Hayes macro-PROCESS. The results indicate a strong positive impact of organizational learning culture (β = .6; p < .001), with employee resilience serving as a mediator in this relationship (β = .16; 95% CI = [.08, .24]). Additionally, abusive supervision weakens the mediation effect (β = -.04; 95% CI = [-.111, -.002]). These findings hold significant implications for managers and HR professionals, emphasizing the importance of cultivating an organizational learning culture to enhance employee resilience, better equip employees to navigate competitive markets and maintain high levels of employee engagement.